Correlation Of Asphyxia Neonatorum Incidence And Caesarean Section Delivery - Yofita, Fransiska; Ruddy, B. Triagung; Sincihu, Yudhiakuari (JOURNAL OF WIDYA MEDIKA JUNIOR, 2019)
Introduction: Asphyxia neonatorum occupies second place in the cause of death of babies in East Java in 2010 and still in the top three of the cause of death of babies in Surabaya until 2016. One of the risk factors of asphyxia neonatorum was the delivery method, one of which is caesarean section delivery. Aim: The purpose of this study was to determine the correlation between asphyxia neonatorum incidence and caesarean section delivery. Methods: This is an observational analytical study using secondary data with retrospective approach. This study used case control design. Total population in this study were 1112 birthing mother and 1134 babies born during 1 January 2016 until 31 December 2016. A total of 125 case samples (Asphyxia) were chosen using purposive sampling technique, while 125 control samples (No asphyxia) were chosen using simple random sampling technique. Data were analysed with Chi-Square test. Results: Results showed that there were no significant correlation between asphyxia neonatorum incidence and caesarean section delivery (p = 0.591) Conclusion: This study showed that caesarean section delivery was not the main risk factor of asphyxia neonatorum.